An empirical study: Characteristics of business entities and corporate governance on risk disclosure practices - Arfan Amrin (Verslas: Teorija ir praktika / Business: Theory and Practice, 2019)
This paper investigates the association between the characteristics of business entities, corporate governance, and practices of risk disclosure. Notably, the objective of this paper is to examine the impact of the characteristics of business entities and corporate governance on risk disclosure in non-financial companies. The samples used in this study included 312 non-financial companies registered on the Indonesia Stock Exchange. The hypothesis testing in this paper using regression analysis. The results of this paper indicate that the size of the audit committee (SAC), the availability of risk monitoring or risk management committees (RMC) and the quality of external auditors (AUD) are significantly associated with corporate risk disclosure practices (CRD). These empirical results show that the presence of risk monitoring committee, the quality of external auditors, and the size of the audit committee are the main factors determining the extent of risk disclosure, especially for non-financial companies listed on the Indonesia Stock Exchange. This paper also shows that the age of business entities has a negative impact on corporate risk disclosure practices.
Keywords: M21; M40; M41; 650; characteristics; business entity; corporate governance; risk disclosure; non-financial companies